The Distribution and Community’s Perception of Flying Fox, Pteropus vampyrus in Limbang, a Transboundary Area in Sarawak - Jayasilan Mohd-Azlan,; Sally Soo Kaicheen,; Lisa Lok, (Tropical Life Sciences Research, 2022)
Flying foxes are threatened throughout their geographic range, and there are large gaps in the understanding of their landscape-scale habitat use. This study identified potential habitats in Limbang, Sarawak and informed potential distribution based on dispersal and interview surveys. Here, biological surveys were combined with interviews of local communities in Limbang Mangrove National Park (LMNP), Sarawak to illustrate distribution and the communities' perception on the protected flying fox (Pteropus vampyrus). Mangrove forest areas were surveyed for for the presence of flying foxes and villagers were interviewed regarding the use by flying foxes of agricultural areas and instances of conflict. Boat and questionnaire surveys were conducted for nine days from 18 to 27 February 2021. The surveys did not record any flying fox roosting sites within the national park and was instead observed to fly from Menunggul Island, Brunei into the national park in the evenings and back to Brunei in the mornings. A total of 27 flying foxes were recorded during the boat survey. Flying foxes were detected from 8/154 survey points and their spatial distribution appeared to be concentrated along Sungai Limpaku Pinang. Most respondents were aware of the species while some have directly observed them in fruit orchards, mangroves, rivers and mixed dipterocarp forests. Eleven perception-based questions were presented, and results showed that locality and income were the most influential parameters exhibiting conservation awareness through Boosted Regression Trees (BRT) analysis. Most respondents believe that flying foxes can uplift the local economy through ecotourism opportunities. However, these findings need to be carefully interpreted as the species has a large home range. Hence, long-term monitoring should be established to generate a larger dataset for stronger analysis to better represent the distribution and occurrence of this species in LMNP. Keluang adalah spesies terancam di seluruh kawasan taburan mereka, dan terdapat jurang yang besar dalam pemahaman penggunaan habitat berskala landskap spesies ini. Kajian ini bertujuan untuk mengenal pasti habitat berpotensi untuk keluang di tinjauan bot dan soal selidik di Limbang dapat menggambarkan taburan dan persepsi masyarakat terhadap keluang di Limbang, Sarawak. Tinjauan terhadap keluang di kawasan hutan bakau di Limbang telah dilakukan dan penduduk kampung tempatan di sekitar Taman Negara Bakau Limbang (TNBL) telah disoal selidik selama sembilan hari dari 18 hingga 27 Februari 2021. Tinjauan tidak merekodkan kawasan sarang keluang di dalam taman negara. Namun, keluang kelihatan terbang dari Pulau Menunggul, Brunei ke taman negara tersebut pada waktu petang dan kembali ke Brunei pada waktu pagi. Sebanyak 27 ekor keluang telah direkodkan melalui tinjauan bot. Keluang dikesan dari 8/154 tempat tinjauan dan taburannya didapati tertumpu di sepanjang Sungai Limpaku Pinang. Kebanyakan responden mengenali spesies tersebut manakala ada yang memerhati secara langsung di kebun buah-buahan, bakau, sungai dan hutan dipterokarp. Sebelas soalan berasaskan persepsi telah dikemukakan dan keputusan menunjukkan lokaliti dan pendapatan merupakan parameter yang paling berpengaruh melalui analisis Boosted Regression Trees (BRT). Kebanyakan responden percaya bahawa keluang mampu meningkatkan ekonomi tempatan melalui peluang eko-pelancongan. Walau bagaimanapun, hasil soal selidik ini perlu ditafsirkan dengan teliti kerana spesies ini mempunyai kawasan taburan yang luas. Oleh demikian, pemantauan jangka panjang harus dijalankan bagi menjana set data yang lebih besar untuk analisis yang lebih kukuh untuk mewakili pengedaran dan kejadian spesies ini dengan teliti dalam TNBL.